Mortality and pulmonary complications in patients undergoing upper extremity surgery at the peak of the SARS-CoV-2 pandemic in the UK: a national cohort study - Dean, B; Furniss, D; Carr, A; Cook, J; The Corona Hands Collaborative (BMJ Publishing Group, 2020)
Introduction: This study reports the 30-day mortality, SARS-CoV-2 complication rate and SARS-CoV-2 related hospital processes at the peak of the first wave of the pandemic in the UK.